(untitled) (Economic and Political Thought, 2013)
The author tries to answer the question about the mechanism of historic events, which initially look unimportant but from the time perspective form a logic of some kind of optimum, which for the revolt initiators turns out to be the reverse of their initial intentions. The author highlights a noticeable regularity, which he calls a ‘rule of a reversed optimum’: a characteristic feature of great social changes is that they disrupt the commonly accepted values but in consequence the new ones do not have to create a higher level and optimization of individual parts of the system does not go hand in hand with maintaining the optimum for it as a whole. That is what the social mechanism of great breakthroughs consists in. Their essence is that they are mainly connected with great property redistribution from former owners to the new ones. The beneficiaries feel satisfied even if from the macro-economic point of view the effectiveness of the whole system deteriorates. Contrary to the moralistic interpretation of history, which suspects the existence of some kind of ‘historic keynote’ supposedly aimed at achieving higher and higher social optimum, the real changes take place abruptly and rather disorderly, in accordance with a particular rule of a reversed optimum being a denial of a macro-social optimum. The rule of a reversed optimum makes them play the role of objects rather than initiators.